Transcriptome Analysis Reveals Molecular Underpinnings of Common Carp (Cyprinus carpio) Under Hypoxia Stress - Suo, Ning; Zhou, Zhi-Xiong; Xu, Jian; Cao, Ding-Chen; Wu, Bi-Yin; Zhang, Han-Yuan; Xu, Peng; Zhao, Zi-Xia (Frontiers in Genetics, 2022)
As an essential environmental factor that affects the economic benefits of aquaculture, hypoxia is one of the urgent problems to be solved in the aquaculture fish breeding industry. Common carp (Cyprinus carpio) is a critical economic fish in China, and at present, there are many breeding strains of common carp with different character advantages in China, including Hebao red carp (C. carpio var wuyuanesis), Songpu mirror carp (C. carpio var specularis). Even if the environmental adaptation of common carp is generally strong, the genetic background of hypoxia tolerance in different strains of common carp is unclear yet. This study tested the hypoxia tolerance of Songpu minor carp, Hebao red carp, and their hybrid F1 population by an acute hypoxia treatment. Muscle and liver tissues were used for transcriptome sequencing analysis to identify the key factors for hypoxia tolerance and explore the potential genetic mechanism for breeding high hypoxia tolerance in common carp. The comparative transcriptomic analysis revealed abundant hypoxia response-related genes, and their differential regulation mechanism in these two tissues of different common carp strains under acute hypoxia, including immune response, cellular stress response, HIFs (hypoxia-inducible factors), MAP kinase, iron ion binding and heme binding. Our findings will facilitate future investigation on the hypoxia response mechanism and provide a solid theoretical basis for breeding projects in common carp.